Le village de Noli en Ligurie occidentale entre l’Antiquité tardive et le haut Moyen Âge - Paolo de Vingo (Archéologie Médiévale)
New and extensive excavations have been carried out over the last three years at Noli, in central-western Liguria, a site already known for the archaeological exploration around the church of San Paragorio which began in the 1970s. These recent investigations, in two distinct areas, have not only confirmed a Roman presence prior to the emergence of the Early Medieval village unearthed before the 1990s, but has also produced documented evidence of a settlement that developed during the early Roman Republic, and continued into the 10th century. In this paper the author analyses the processes involved in the formation of the Roman settlement and its conversion into an Early Medieval village : corresponding archaeological data has confirmed the co-existence of residential areas and buildings where various types of production activities were carried out.